Medicine price surveys, analyses and comparisons : evidence, methodology and guidance - Vogler, Sabine M. (Elsevier/Academic Press, 2019)
Medicine Price Surveys, Analyses and Comparisons establishes guidelines for the study and implementation of pharmaceutical price surveys, analyses, and comparisons. Its contributors evaluate price survey literature, discuss the accessibility and reliability of data sources, and provide a checklist and training kit on conducting price surveys, analyses, and comparisons. Their investigations survey price studies while accounting for the effects of methodologies and explaining regional differences in medicine prices. They also consider policy objectives such as affordable access to medicines and cost-containment as well as options for improving the effectiveness of policies. Provides guidance for planning and implementing pharmaceutical pricing policies and systems. Reviews external price referencing systems. Explains common baselines for interpreting price surveys. Defines pharmaceutical price terminology and nomenclature.